Current Status of Brain Tumor in the Kingdom of Saudi Arabia and Application of Nanobiotechnology for Its Treatment: A Comprehensive Review - Afrasim Moin; Syed Mohd Danish Rizvi; Talib Hussain; D. V. Gowda; Gehad M. Subaiea; Mustafa M. A. Elsayed; Mukhtar Ansari; Abulrahman Sattam Alanazi; Hemant Yadav (Life, 2021)
Objective: Brain tumors are the most challenging of all tumors and accounts for about 3% of all cancer allied deaths. The aim of the present review is to examine the brain tumor prevalence and treatment modalities available in the Kingdom of Saudi Arabia. It also provides a comprehensive analysis of the application of various nanotechnology-based products for brain cancer treatments along with their prospective future advancements. Methods: A literature review was performed to identify and summarize the current status of brain cancer in Saudi Arabia and the scope of nanobiotechnology in its treatment. Results: Depending upon the study population data analysis, gliomas, astrocytoma, meningioma, and metastatic cancer have a higher incidence rate in Saudi Arabia than in other countries, and are mostly treated in accordance with conventional treatment modalities for brain cancer. Due to the poor prognosis of cancer, it has an average survival rate of 2 years. Conventional therapy includes surgery, radiotherapy, chemotherapy, and a combination thereof, but these do not control the disease’s recurrence. Among the various nanomaterials discussed, liposomes and polymeric nanoformulations have demonstrated encouraging outcomes for facilitated brain cancer treatment. Conclusions: Nanomaterials possess the capacity to overcome the shortcomings of conventional therapies. Polymer-based nanomaterials have shown encouraging outcomes against brain cancer when amalgamated with other nano-based therapies. Nonetheless, nanomaterials could be devised that possess minimal toxicity towards normal cells or that specifically target tumor cells. In addition, rigorous clinical investigations are warranted to prepare them as an efficient and safe modality for brain cancer therapy.